2023
DOI: 10.1007/s00784-022-04848-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hyaluronic acid, hypochlorous acid, and flurbiprofen on postoperative morbidity in palatal donor area: a randomized controlled clinical trial

Abstract: Objective This study aims to evaluate the effects of topical hyaluronic acid (HA), hypochlorous acid (HOCl), and flurbiprofen on postoperative morbidity of palatal donor sites after free gingival graft (FGG) surgery. Materials and methods Sixty patients requiring FGG were randomly assigned into four groups: control, HA gel (600 mg/100 g high molecular weight hyaluronic acid), HOCl spray (170–200 ppm, ph7.1), flurbiprofen spray (0.075gr flurbiprofen). Topical agents were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Nine RCTs were included in the pairwise meta-analysis (Bitencourt et al, 2022;Castro-Gaspar et al, 2021;Femminella et al, 2016;Hassan et al, 2020;Işler et al, 2019;Morshedzadeh et al, 2022;Patarapongsanti et al, 2019;Pekbagriyanik et al, 2021;Yilmaz, Comerdov, et al, 2022) and 7 RCTs were included in NMA (Bitencourt et al, 2022;Femminella et al, 2016;Hassan et al, 2020;Işler et al, 2019;Morshedzadeh et al, 2022;Patarapongsanti et al, 2019;Pekbagriyanik et al, 2021) for pain assessment (using Seven RCTs were included in pairwise meta-analysis (Alvarez-Medina et al, 2023;Femminella et al, 2016;Heidari et al, 2017;Isler et al, 2018;Morshedzadeh et al, 2022;Patarapongsanti et al, 2019;Pekbagriyanik et al, 2021) and 8 RCTs were include in NMA (open loop of evidence) (Alpan & Cin, 2023;Heidari et al, 2017;Isler et al, 2018;Miguel, Mathias-Santamaria, Rossato, Ferraz, Figueiredo-Neto, et al, 2021, Miguel, Mathias-Santamaria, Rossato, Ferraz, Rangel, et al, 2021Morshedzadeh et al, 2022;Pekbagriyanik et al, 2021;Yilmaz, Kayaalti-Yuksek, & Karaduman, 2022) for the palatal wound complete epithelialization evaluation (using hydrogen peroxide test) after 14-and 21-day. Pairwise meta-analysis for pain assessment and wound healing were reported in the Appendix S1.…”
Section: Results Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Nine RCTs were included in the pairwise meta-analysis (Bitencourt et al, 2022;Castro-Gaspar et al, 2021;Femminella et al, 2016;Hassan et al, 2020;Işler et al, 2019;Morshedzadeh et al, 2022;Patarapongsanti et al, 2019;Pekbagriyanik et al, 2021;Yilmaz, Comerdov, et al, 2022) and 7 RCTs were included in NMA (Bitencourt et al, 2022;Femminella et al, 2016;Hassan et al, 2020;Işler et al, 2019;Morshedzadeh et al, 2022;Patarapongsanti et al, 2019;Pekbagriyanik et al, 2021) for pain assessment (using Seven RCTs were included in pairwise meta-analysis (Alvarez-Medina et al, 2023;Femminella et al, 2016;Heidari et al, 2017;Isler et al, 2018;Morshedzadeh et al, 2022;Patarapongsanti et al, 2019;Pekbagriyanik et al, 2021) and 8 RCTs were include in NMA (open loop of evidence) (Alpan & Cin, 2023;Heidari et al, 2017;Isler et al, 2018;Miguel, Mathias-Santamaria, Rossato, Ferraz, Figueiredo-Neto, et al, 2021, Miguel, Mathias-Santamaria, Rossato, Ferraz, Rangel, et al, 2021Morshedzadeh et al, 2022;Pekbagriyanik et al, 2021;Yilmaz, Kayaalti-Yuksek, & Karaduman, 2022) for the palatal wound complete epithelialization evaluation (using hydrogen peroxide test) after 14-and 21-day. Pairwise meta-analysis for pain assessment and wound healing were reported in the Appendix S1.…”
Section: Results Synthesismentioning
confidence: 99%
“…Seven RCTs were included in pairwise meta‐analysis (Alvarez‐Medina et al., 2023; Femminella et al., 2016; Heidari et al., 2017; Isler et al., 2018; Morshedzadeh et al., 2022; Patarapongsanti et al., 2019; Pekbagriyanik et al., 2021) and 8 RCTs were include in NMA (open loop of evidence) (Alpan & Cin, 2023; Heidari et al., 2017; Isler et al., 2018; Miguel, Mathias‐Santamaria, Rossato, Ferraz, Figueiredo‐Neto, et al., 2021, Miguel, Mathias‐Santamaria, Rossato, Ferraz, Rangel, et al., 2021; Morshedzadeh et al., 2022; Pekbagriyanik et al., 2021; Yilmaz, Kayaalti‐Yuksek, & Karaduman, 2022) for the palatal wound complete epithelialization evaluation (using hydrogen peroxide test) after 14‐ and 21‐day. Pairwise meta‐analysis for pain assessment and wound healing were reported in the Appendix S1.…”
Section: Resultsmentioning
confidence: 99%
“…The HA concentration in the commercially available products containing high molecular weight HA is in the range of 0.2–0.8% [ 16 , 18 ]. The concentration, treatment protocol, and frequency may have affected the different clinical results reported in the previous studies [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…HA may accelerate wound healing through blood clot stabilization, decreased inflammatory responses, neovascularization, angiogenesis, increased fibroblast migration, and wound closure [ 16 , 18 ]. A meta-analysis reported that the laser-assisted labial frenectomy decreased the need for the administration of postoperative analgesics; however, no significant difference was observed between the laser-assisted frenectomy and conventional technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation